Solid polymer electrolyte membrane solvent annealing modification method and secondary ion battery application thereof
By using solvent annealing devices in solid polymer electrolyte membranes to regulate gas flow and heaters, the problems of low room temperature ion conductivity and high interface resistance of solid electrolyte membranes are solved, and the energy density and process stability of the battery are improved. It is suitable for Large-scale production of secondary ion batteries.
Patent Information
- Application Number
- CN202410994553.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
All-solid polymer electrolytes have room for improvement in high room temperature ionic conductivity, low electrolyte/electrode interface resistance and high energy density. The existing solvent annealing process has poor stability and reliability, and insufficient electrochemical stability window and high voltage resistance performance. .
The solvent annealing device is used to modify the solid polymer electrolyte membrane. By annealing in a solvent atmosphere, the gas flow rate and heater are regulated to remove residual solvents, the polymer molecular chain movement ability is improved, the interface resistance is reduced, and it is suitable for a variety of solvents. .
It realizes surface softening of the solid electrolyte membrane, reduces the interface impedance of the electrolyte/electrode, improves room temperature ion conductivity, enhances battery energy density, improves process stability and reliability, and is suitable for large-scale production.
Smart Images

Figure CN119133584A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid-state batteries, and in particular relates to a modification method of a solid polymer electrolyte membrane by solvent annealing and an application thereof in a secondary ion battery. Background Art
[0002] All-solid-state batteries use solid electrolytes to replace the electrolyte and separator of traditional secondary ion batteries. They are safer, have higher energy density, and have stronger cycle performance. They have become the main research and development direction of the next generation of power batteries recognized by the industry. Solid electrolytes are the core components of all-solid-state batteries, and they have the following basic characteristics: high ionic conductivity, high ion migration number, good solid-solid interface compatibility, excellent electrochemical stability and mechanical properties. Among them, polymer solid electrolytes have excellent mechanical properties, can be used to prepare large-capacity batteries, are easy to process, and have preparation processes and electrochemical properties similar to existing commercial secondary ion batteries based on liquid electrolytes. They are currently recognized as the solid-state batteries closest to mass production.
[0003] At present, all-solid polymer electrolytes still have a lot of room for improvement in terms of high room temperature ionic conductivity, low electrolyte / electrode interface resistance, and high energy density. In order to improve the room temperature ionic conductivity of all-solid polymer electrolytes, the polymer matrix is usually doped or modified to inhibit polymer crystallization or reduce its glass transition temperature; the operation process is often complicated and has poor reliability. In order to reduce the interface resistance of electrolyte / electrode materials, researchers usually use liquid electrolytes to drip between the interfaces or apply high pressure at both ends of the battery to improve the interface contact; the process reliability is poor. At the same time, some researchers have tried to prepare solid polymer electrolytes by in-situ polymerization, which can preliminarily solve the problems of low room temperature ionic conductivity and high electrolyte / electrode interface impedance. However, at this stage, the process still has problems such as difficult to control the reaction process, small molecule residues in the reaction products, and complex polymerization process. There are relatively few research reports on high energy density, which are often achieved by selecting a high-voltage resistant polymer matrix or adding inorganic fillers to the polymer matrix to prepare polymer composite solid electrolytes; compared with other solid electrolyte materials such as sulfides and oxides, polymer solid electrolytes have poor performance in electrochemical stability window and high voltage resistance. Therefore, the development of high-capacity polymer secondary ion batteries often starts with improving the compatibility with high-capacity positive and negative electrode materials. For example, polymer solid electrolytes can be matched with lithium metal negative electrodes to assemble lithium metal batteries; compared with commercial liquid electrolytes and graphite negative electrodes, secondary lithium-ion batteries have higher energy density.
[0004] Patent CN201980029915.6 discloses a method for manufacturing an electrode containing a polymer solid electrolyte and an electrode manufactured by the method. The solvent annealing process and annealing effect used are easily affected by the initial state of the sample, the surrounding environment, the characteristics of the solvent molecules themselves, etc., and the process stability and reliability are poor. For example: if there is water or other solvent residue in the sample, it will have a significant impact on the annealing effect, and the process described therein cannot remove the residual solvent; on the contrary, the process described in this patent can be purged by a large amount of dry gas to take away most of the residual solvent and ensure the repeatability of the annealing process. In addition, there is no temperature control device in patent CN201980029915.6, and it is well known that temperature has a greater impact on the saturated vapor pressure of the solvent, which will interfere with the stability of the solvent annealing process. In addition, the characteristics of the solvent molecules themselves, such as the saturated vapor pressure, have a greater impact on the solvent annealing process. This patent can regulate the content of solvent molecules entering the annealing chamber by regulating the gas flow rate and heating, and the process has obvious flexibility and reliability.
[0005] Therefore, how to provide a simple and easy-to-scalable method to solve the problems of low room temperature ionic conductivity, high electrolyte / electrode interface impedance, and low battery energy density of all-solid-state polymer electrolyte film samples is a technical problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to provide a modification method of a solid polymer electrolyte membrane by solvent annealing and its application in secondary ion batteries in view of the above-mentioned deficiencies in the prior art, so as to achieve surface softening of the solid polymer electrolyte membrane by solvent annealing, improve its contact with the solid electrode material, reduce the interface resistance between the electrolyte / electrode, and facilitate the transmission of metal cations during the charge and discharge process.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The first object of the present invention is to provide a modification method for solvent annealing of a solid polymer electrolyte membrane, wherein the solid polymer electrolyte membrane is placed in a solvent annealing device and annealed in a solvent atmosphere for 30-7200 seconds. The solvent annealing device comprises a solvent storage tank, an annealing chamber, a heater and an external gas. The solvent storage tank is connected to the annealing chamber through a pipeline. A solid electrolyte membrane can be placed in the annealing chamber. The heater is arranged below the solvent storage tank to adjust the saturated vapor pressure of the solvent in the solvent storage tank as needed. The external gas provides gas to the solvent storage tank so that the solvent in the solvent storage tank is partially vaporized. The gas flow carrying the solvent molecules enters the annealing chamber along the pipeline and contacts the solid electrolyte membrane, and then enters the solid electrolyte membrane to complete solvent annealing.
[0009] Furthermore, the solvent storage tank is connected to the external gas through a first gas pipeline, the annealing chamber is connected to the solvent storage tank through a second gas pipeline, the annealing chamber is connected to the first gas pipeline through a third gas pipeline, and the second gas pipeline is connected to the third gas pipeline.
[0010] Furthermore, a sealing cover is provided on the top of the annealing chamber, and the first gas pipeline and the second gas pipeline are respectively penetrated through the sealing cover and arranged in the solvent storage tank, one end of the first gas pipeline is inserted into the solvent, and the other end of the first gas pipeline is connected to the external gas; one end of the second gas pipeline is located above the solvent, and the other end of the second gas pipeline is connected to the third gas pipeline, and the third gas pipeline is provided with a flow control valve.
[0011] Furthermore, the external gas is a dry inert gas.
[0012] Furthermore, the residual solvent molecules in the solid electrolyte membrane can be removed by purging a large amount of dry inert gas, and the process stability can be achieved by controlling the purging time.
[0013] Furthermore, the content of solvent molecules in the gas in the annealing chamber can be flexibly controlled by regulating the flow rate of the external gas and controlling the temperature of the solvent storage tank, which is flexible and reliable.
[0014] Furthermore, the solvent in the solvent storage tank includes any one or more of esters, ethers, nitriles, ketones, aromatic hydrocarbons, sulfones, sulfoxides, carboxylates and amides.
[0015] The second object of the present invention is to provide a surface-modified solid polymer electrolyte membrane prepared by the above-mentioned modification method.
[0016] The third object of the present invention is to provide the use of the above-mentioned surface-modified solid polymer electrolyte membrane in the preparation of secondary ion batteries.
[0017] Furthermore, the secondary ion battery includes any one of a lithium secondary battery, a zinc secondary battery, a potassium secondary battery and a sodium secondary battery.
[0018] A fourth object of the present invention is to provide a secondary ion battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator comprises the above-mentioned surface-modified solid polymer electrolyte membrane.
[0019] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0020] (1) The present invention provides a modification method of a solid polymer electrolyte membrane by solvent annealing, which can soften the surface of the solid polymer electrolyte membrane by solvent annealing, improve its contact with the solid electrode material, reduce the interfacial resistance between the electrolyte / electrode, and facilitate the transmission of metal cations during the charge and discharge process. The complexation between the solvent molecules and the polymer and the electrolyte salt is conducive to the dissociation of the electrolyte salt, thereby obtaining more metal cations that can diffuse freely during the charge and discharge process. In addition, a small amount of complexing solvent molecules can improve the mobility of the polymer molecular chain, which is reflected in inhibiting the crystallization of the polymer or reducing the glass transition temperature of the polymer chain. The improvement of the mobility of the polymer molecular chain is conducive to the diffusion of the dissociated metal cations, thereby obtaining a polymer electrolyte membrane material with high room temperature ionic conductivity.
[0021] (2) The modification method provided by the present invention can effectively reduce the influence of residual solvent molecules in the unannealed solid polymer electrolyte membrane and improve the reliability of the annealing process;
[0022] (3) The modification method provided by the present invention can be based on temperature control and gas flow control technology, and is widely applicable to solvent molecules with different physical properties, and the content of solvent molecules in the gas entering the annealing chamber can be flexibly controlled as needed;
[0023] (4) The modification method provided by the present invention can stably control the content of solvent molecules in the gas entering the annealing chamber, and the process is reliable;
[0024] (5) The modification method provided by the present invention is compatible with the existing secondary battery assembly process and is convenient for large-scale production.
[0025] (6) The surface-modified solid polymer electrolyte membrane provided by the present invention can avoid the introduction of free solvent molecules, and thus can be assembled with metal negative electrodes such as lithium, zinc, and sodium into a high-capacity metal battery with stable operation.
[0026] (7) Both the electrode and the polymer electrolyte membrane are solvent annealed, and the electrolyte-electrode interface contact and interfacial compatibility are good after the assembled battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 A schematic structural diagram of a solvent annealing device for solid polymer electrolyte membrane modification provided by the present invention;
[0028] Figure 2 A schematic diagram of the principle of solvent annealing modification provided by the present invention;
[0029] Figure 3 A schematic diagram of the assembly of a soft-pack battery provided by the present invention;
[0030] Figure 4 This is a schematic diagram of the assembly of the button battery provided by the present invention.
[0031] In the figure, 1. solvent storage tank; 2. annealing chamber; 3. heater; 4. external gas; 5. first gas pipeline; 6. second gas pipeline; 7. third gas pipeline; 8. sealing cover; 9. flow control valve; 10. solid electrolyte membrane. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0033] refer to Figure 1 , a schematic structural diagram of a solvent annealing device for solid polymer electrolyte membrane modification provided by the present invention, the solvent annealing device comprises a solvent storage tank 1, an annealing chamber 2, a heater 3 and an external gas 4, the solvent storage tank 1 is connected with the annealing chamber 2 through a pipeline, a solid electrolyte membrane 10 can be placed in the annealing chamber 2, the heater 3 is arranged below the solvent storage tank 1, the saturated vapor pressure of the solvent in the solvent storage tank 1 is regulated by temperature, the external gas 4 provides gas to the solvent storage tank 1 so that the solvent in the solvent storage tank 1 is partially atomized, and the gas carrying solvent molecules enters the annealing chamber 2 along the pipeline, contacts the solid electrolyte membrane, and then enters the solid electrolyte membrane to complete solvent annealing.
[0034] In some embodiments, in order to better control the effect of solvent annealing so that the modified solid polymer electrolyte membrane obtains a higher room temperature ionic conductivity, the solvent storage tank 1 can be connected to the external gas 4 through the first gas pipeline 5, the annealing chamber 2 is connected to the solvent storage tank 1 through the second gas pipeline 6, the annealing chamber 2 is connected to the first gas pipeline 5 through the third gas pipeline 7, and the second gas pipeline 6 is connected to the third gas pipeline 7.
[0035] In some embodiments, in order to facilitate the operation of the staff, a sealing cover 8 can be provided on the top of the annealing chamber 2, and the first gas pipeline 5 and the second gas pipeline 6 are respectively penetrated through the sealing cover 8 and arranged in the solvent storage tank 1, one end of the first gas pipeline 5 is inserted into the solvent, and the other end of the first gas pipeline 5 is connected to the external gas 4; one end of the second gas pipeline 6 is located above the solvent, and the other end of the second gas pipeline 6 is connected to the third gas pipeline 7, and the third gas pipeline 7 is provided with a regulating valve 9.
[0036] In some embodiments, the external gas 4 is not limited, and a dry inert gas may be selected and introduced into the solvent storage tank to cause the solvent to bubble to generate solvent vapor, preferably argon.
[0037] In some embodiments, the solid electrolyte membrane and the solvent are not limited, and a suitable solvent can be selected according to the types of polymer and electrolyte salt in the solid polymer electrolyte membrane. The solvent requirements are: 1) it can act as a plasticizer to improve the mobility of polymer chain segments; 2) it can dissociate electrolyte salts; 3) it can be volatile.
[0038] In some embodiments, the solid electrolyte membrane 10 can be selected from polyethylene oxide (PEO), polymethyl methacrylate (PMMA) and block copolymers thereof as polymer matrices, and electrolyte membranes based on lithium bis(trifluoromethylsulfonyl)amide (LiTFSI) and zinc trifluoromethanesulfonate (Zn(OTF)2). PEO and PMMA contain ether bonds and ester bonds, respectively, and can be complexed with secondary ion salts such as lithium, sodium, and zinc to promote the dissociation of salts and are widely used. LiTFSI and Zn(OTF)2 are currently commonly used electrolyte salts for secondary lithium ion and zinc ion batteries due to their high ionic conductivity and excellent air stability.
[0039] In some embodiments, the solvent filled in the solvent storage tank can be a volatile solvent such as esters, ethers, nitriles, ketones, aromatic hydrocarbons, sulfones, sulfoxides, carboxylates and amides, and specifically can be one or more of methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, amyl acetate, methyl propionate, ethyl propionate, butyl propionate, propylene carbonate, acetone, methyl ethyl ketone, tetrahydrofuran, 1,3-dioxolane, ethylene glycol dimethyl ether, acetonitrile, ethyl ether, toluene, xylene, methanol, ethanol, propanol, n-butanol, isopropanol, decalin, and acetic acid.
[0040] In some embodiments, the solvent annealing device provided by the present invention can also simultaneously modify the electrode surface.
[0041] The working process of the solvent annealing device provided by the present invention is specifically as follows: an external gas 4 is introduced into the content of the solvent storage tank 1 to partially atomize the solvent to generate solvent vapor, and the solvent vapor is sent into the annealing chamber by using the dry external gas 4; the bubbling process can also use a heater 3 to accelerate the volatilization of the solvent, and the air flow rate can be controlled by a flow control valve 9. The annealing chamber 2 can accommodate multiple solid polymer electrolyte films and electrodes. The solid polymer electrolyte film and the electrode are suspended in the annealing chamber 2 to ensure that the film and the electrode can be fully in contact with the solvent vapor, thereby reducing the processing time. As time goes by, the solvent evaporates, and a large amount of gaseous solvent small molecules contact the film and the electrode and enter the film and electrode body phase to complete the solvent annealing. The time is controlled, the polymer electrolyte membrane and the electrode after solvent annealing are taken out of the container, and the free solvent molecules that may exist on the surface of the electrolyte membrane are removed by wiping, high-temperature drying in a vacuum oven, and standing in a glove box, etc., to obtain a polymer electrolyte membrane and electrode with solvent annealing surface modification.
[0042] refer to Figure 2 , which is a schematic diagram of the principle of solvent annealing modification provided by the present invention. The complexation between the solvent molecules and the polymer and the electrolyte salt is conducive to the dissociation of the electrolyte salt, thereby obtaining more metal cations that can diffuse freely during the charge and discharge process. A small amount of complexing solvent molecules can improve the mobility of the polymer molecular chain, which is reflected in inhibiting the crystallization of the polymer or reducing the glass transition temperature of the polymer chain. The improvement of the mobility of the polymer molecular chain is conducive to the diffusion of the dissociated metal cations, thereby obtaining a polymer electrolyte membrane with high room temperature ionic conductivity.
[0043] Free solvent molecules that may exist on the surface of the polymer electrolyte membrane after annealing are removed by wiping, high-temperature vacuum treatment, etc., to prevent side reactions with the metal negative electrode. The modified solid polymer electrolyte membrane of the present invention does not contain free solvent molecules, so it can be assembled with metal negative electrodes such as lithium, zinc, and sodium into a stable and high-capacity metal battery. Due to its good flexibility and processability, the polymer electrolyte membrane can be assembled into button cells or soft-pack batteries using existing commercial secondary lithium-ion battery assembly processes. Because metal negative electrodes such as lithium, zinc, and sodium have higher theoretical energy densities than negative electrode materials such as graphite, hard carbon, and secondary ion metal compounds, the method provided by the present invention can prepare metal batteries with higher energy density than commercial secondary ion batteries.
[0044] The following is a specific example to illustrate how to obtain a polymer electrolyte membrane with high room temperature ionic conductivity.
[0045] Example 1
[0046] This embodiment provides an electrolyte membrane modified by annealing with tetrahydrofuran solvent and a lithium metal battery assembly.
[0047] Lithium bis(trifluoromethylsulfonyl)amide (LiTFSI) and polymethyl methacrylate grafted natural rubber (MG30) are used as electrolyte salt and polymer matrix materials respectively; tetrahydrofuran is used as solvent for solvent annealing, and acetonitrile, acetone, chloroform, benzene, and toluene can also be used as solvents; lithium iron phosphate is used as positive electrode material, and lithium cobalt oxide, lithium manganese oxide, and nickel cobalt manganese ternary materials can also be used as positive electrodes; lithium metal is used as negative electrode material. LiTFSI and MG30 are mixed in a ratio of Li to MMA molar ratio of 2:1 using melt mixing technology (patent number: ZL202011643287.1 and ZL202010041632.8) using a double-drum mixer to prepare a solid polymer electrolyte film MG30 / LiTFSI. Then, the sample is transferred to a glove box with an argon atmosphere and allowed to stand for 1 to 2 weeks until the residual water vapor is completely volatilized to obtain a MG30 / LiTFSI solid polymer electrolyte film. The solid electrolyte film was transferred to the annealing chamber and purged with dry argon for 1 hour to reduce and stabilize the content of possible residual solvent in the sample. An appropriate amount of tetrahydrofuran was poured into the solvent storage bottle, the temperature was controlled at 30°C, and the flow rate of argon entering the storage bottle was controlled (the number of bubbles generated in the solvent per minute was 25). The annealing experiment was completed according to the annealing time set in the experiment (90min). The solvent-annealed electrolyte film was carefully removed from the annealing chamber, and the solvent on the surface of the sample was carefully wiped off with lens paper, and then the sample was left to stand in the glove box (argon atmosphere) for 1 to 10 hours to ensure that the free tetrahydrofuran solvent molecules were removed. The room temperature ionic conductivity of the obtained electrolyte membrane (MG30 / LiTFSI / THF) was measured by electrochemical impedance spectroscopy. The room temperature ionic conductivity of MG30 / LiTFSI / THF is 0.9×10 -3 S / cm, which is much higher than that of MG30 / LiTFSI solid polymer electrolyte film without solvent annealing interface modification ~4.1×10 -7 S / cm. The oxidation potential of MG30 / LiTFSI / THF was measured by linear sweep voltammetry (LSV) to be 5.14V. The electrolyte membrane was assembled into a Li|MG30 / LiTFSI / THF|LFP full battery with the previously prepared positive and negative electrodes for battery performance testing. Tested at 30°C, the discharge specific capacities at current densities of 0.1C, 0.2C, 0.5C, and 1C were 139.8, 136.9, 128.6, and 101.7 mAh / g, respectively, and the discharge specific capacity recovered to 138.1 mAh / g when returning to 0.1C.
[0048] Example 2
[0049] This embodiment provides an electrolyte membrane modified by annealing with acetonitrile solvent and a lithium metal battery assembly.
[0050] Lithium bis(trifluoromethylsulfonyl)amide (LiTFSI) and polymethyl methacrylate grafted natural rubber (MG30) are used as electrolyte salt and polymer matrix materials respectively; acetonitrile is used as solvent for solvent annealing; lithium iron phosphate is used as positive electrode material, and lithium cobalt oxide, lithium manganese oxide, and nickel cobalt manganese ternary materials can also be used for the positive electrode; lithium metal is used as negative electrode material. The solid electrolyte film is transferred to the annealing chamber and purged with dry argon for 1 hour to reduce and stabilize the content of possible residual solvent in the sample. As in Example 1, an appropriate amount of acetonitrile is poured into the solvent storage bottle, the temperature is controlled at 30°C, and the flow rate of argon entering the storage bottle is controlled (the number of bubbles generated in the solvent per minute is 30). According to the annealing time set in the experiment (60min), the annealing experiment is completed. Carefully remove the electrolyte film after solvent annealing from the container, and carefully wipe the solvent on the surface of the sample with lens paper, and then let the sample stand in a glove box (argon atmosphere) for 1 to 10 hours to ensure that the free acetonitrile solvent molecules are removed. The room temperature ionic conductivity of the obtained electrolyte membrane (MG30 / LiTFSI / AN) was measured by electrochemical impedance spectroscopy. The room temperature ionic conductivity of the obtained sample was 7.75×10 -3 S / cm, which is much higher than that of MG30Li2 solid polymer electrolyte film without solvent annealing interface modification ~4.1×10 -7 The oxidation potential of MG30 / LiTFSI / AN was measured by linear sweep voltammetry (LSV) and was found to be 3.9 V.
[0051] Example 3
[0052] This embodiment provides an electrolyte membrane modified by annealing with acetone solvent and a lithium metal battery assembly.
[0053] Lithium bis(trifluoromethylsulfonyl)amide (LiTFSI) and polymethyl methacrylate grafted natural rubber (MG30) are used as electrolyte salt and polymer matrix materials respectively; acetone is used as solvent for solvent annealing; lithium iron phosphate is used as positive electrode material, and lithium cobalt oxide, lithium manganese oxide, and nickel cobalt manganese ternary materials can also be used for the positive electrode; lithium metal is used as negative electrode material. The solid electrolyte film is transferred to the annealing chamber and purged with dry argon for 1 hour to reduce and stabilize the content of possible residual solvent in the sample. As in Example 1, an appropriate amount of acetone is poured into the solvent storage bottle, the temperature is controlled at 30°C, and the flow rate of argon entering the storage bottle is controlled (the number of bubbles generated per minute in the solvent is 28). According to the annealing time set in the experiment (45min), the annealing experiment is completed. Carefully remove the electrolyte film after solvent annealing from the container, and carefully wipe the solvent on the surface of the sample with lens paper, and then let the sample stand in a glove box (argon atmosphere) for 1 to 10 hours to ensure that the free acetone solvent molecules are removed. The room temperature ionic conductivity of the obtained electrolyte membrane was measured by electrochemical impedance spectroscopy. The room temperature ionic conductivity of the obtained sample was 8.33×10-4 S / cm, which is much higher than that of MG30 / LiTFSI solid polymer electrolyte film without solvent annealing interface modification ~4.1×10 -7 The oxidation potential of the polymer electrolyte film after annealing in acetone was measured by linear sweep voltammetry (LSV) to be 4.1 V.
[0054] Example 4
[0055] This embodiment provides an annealing process using different solvents, and the treatment process is basically the same as that in Example 1.
[0056] The room temperature ionic conductivity results of the solid polymer electrolyte film after treatment with a single solvent are shown in Table 1:
[0057] Table 1.
[0058] Solvent Type Examples <![CDATA[Room temperature ionic conductivity / S cm -1 > Esters Propylene carbonate <![CDATA[~0.4×10 -3 ]]> Ethers Tetrahydrofuran <![CDATA[~0.9×10 -3 ]]> Nitriles Acetonitrile <![CDATA[~3.0×10 -3 ]]> Ketones acetone <![CDATA[~0.4×10 -3 ]]>
[0059] The room temperature ionic conductivity results of the solid polymer electrolyte film after sequential treatment with mixed solvents are shown in Table 2:
[0060] Table 2.
[0061]
[0062] Example 5
[0063] This embodiment provides a soft-pack battery.
[0064] The soft pack battery can be prepared by a common preparation method in the art. Figure 3 The soft pack battery has a positive electrode, a metal negative electrode and a solid polymer electrolyte. The solid polymer electrolyte is sandwiched between the positive electrode and the metal negative electrode. The aluminum-plastic film is connected to the positive electrode and the metal negative electrode, and is electrically connected to the outside through the tab. The solid polymer electrolyte is charged or discharged by the transfer of ions between the positive electrode and the metal negative electrode through the solid polymer electrolyte.
[0065] Example 6
[0066] This embodiment provides a button battery.
[0067] The button cell can be prepared by a common preparation method in the art. Figure 4 The soft pack battery has a positive electrode, a negative electrode and a solid polymer electrolyte. The solid polymer electrolyte is sandwiched between the positive electrode and the negative electrode. The positive electrode and the negative electrode are respectively connected to the external terminal positive electrode shell and the negative electrode shell, and the solid polymer electrolyte is charged or discharged by the transfer of ions between the positive electrode and the negative electrode through the solid polymer electrolyte.
[0068] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for modifying a solid polymer electrolyte membrane by solvent annealing, characterized in that: The solid polymer electrolyte film is placed in a solvent annealing device and annealed in a solvent atmosphere for 30-7200 seconds. The solvent annealing device comprises a solvent storage tank (1), an annealing chamber (2), a heater (3) and an external gas (4). The solvent storage tank (1) is connected to the annealing chamber (2) through a pipeline. A solid electrolyte membrane (10) can be placed in the annealing chamber (2). The external gas (4) provides gas to the solvent storage tank (1) so that the solvent in the solvent storage tank (1) bubbles. The heater (3) is arranged below the solvent storage tank (1) to regulate the saturated solvent vapor pressure in the solvent storage tank (1). Solvent molecules are carried into the annealing chamber (2) by the external gas (4) and come into contact with the solid electrolyte membrane, and then enter the solid electrolyte membrane to complete solvent annealing.
2. The modification method according to claim 1, characterized in that The solvent storage tank (1) is connected to the external gas (4) via a first gas pipeline (5), the annealing chamber (2) is connected to the solvent storage tank (1) via a second gas pipeline (6), the annealing chamber (2) is connected to the first gas pipeline (5) via a third gas pipeline (7), and the second gas pipeline (6) is connected to the third gas pipeline (7).
3. The modification method according to claim 2, characterized in that: A sealing cover (8) is provided on the top of the annealing chamber (2); the first gas pipeline (5) and the second gas pipeline (6) are respectively passed through the sealing cover (8) and are arranged in the solvent storage tank (1); one end of the first gas pipeline (5) is inserted into the solvent, and the other end of the first gas pipeline (5) is connected to the external gas (4); one end of the second gas pipeline (6) is located above the solvent, and the other end of the second gas pipeline (6) is connected to the third gas pipeline (7); and a flow control valve (9) is provided on the third gas pipeline (7).
4. The modification method according to claim 1, characterized in that: The external gas (4) is a dry inert gas.
5. The modification method according to claim 1, characterized in that: The solvent in the solvent storage tank (1) includes any one or more of esters, ethers, nitriles, ketones, aromatic hydrocarbons, sulfones, sulfoxides, carboxylates and amides.
6. The modification method according to claim 1, characterized in that: The residual solvent molecules in the solid electrolyte membrane (10) can be removed by purging a large amount of dry inert gas.
7. A surface-modified solid polymer electrolyte membrane, characterized in that: The method is prepared by the modification method described in any one of claims 1 to 6.
8. Use of the surface-modified solid polymer electrolyte membrane as claimed in claim 7 in the preparation of secondary ion batteries.
9. The use as claimed in claim 8, characterized in that The secondary ion battery includes any one of a lithium secondary battery, a zinc secondary battery, a potassium secondary battery, and a sodium secondary battery.
10. A secondary ion battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The separator comprises the surface-modified solid polymer electrolyte membrane described in claim 7.
Citation Information
Patent Citations
Method for in-situ measurement on solvent steam expansion in polymer film
CN106814056A
Method for manufacturing all-solid-state battery comprising polymer-based solid electrolyte and all-solid-state battery manufactured by same method
CN112055909A
Method for manufacturing electrode comprising polymeric solid electrolyte, and electrode manufactured using same
CN112136233A
All-solid-state polymer electrolyte interface modification method and application of all-solid-state polymer electrolyte interface modification method in secondary ion battery
CN118017043A
